Influência de laminas de chuva no controle de plantas daninhas, semeadas em diferentes profundidades no solo, com aplicação de herbicidas pré-emergentes - Pereira, Maria Renata Rocha [UNESP]; Silva, José Iran Cardoso da [UNESP]; Rodrigues, Andreia Cristina Peres [UNESP]; Martins, Dagoberto [UNESP]; Klar, Antonio Evaldo [UNESP] (My University, 2010)
The aim of this work was to evaluate the control in pre-emergence of the weeds brachiaria grass (Brachiaria decumbens) and goosegrass (Eleusine indica) in different depths in the ground, for the oxyfluorfen and isoxaflutole herbicides, applied in pre-emergence condition and submitted of different rain blades. The experimental design was entirely at random, with four repetitions. Each set was consisted of plastic vases with substratum capacity of 4L, filled with arenaceous ground, increased of brachiaria grass and goosegrass seeds in the depths: 0,5; 1,0; 3,0; 6,0 and 9,0 cm. Doses of 37,5 g a.i. ha -1 of isoxaflutole and 720 g a.i. ha -1 of oxyfluorfen were used. The rain blades was 5, 10 and 20 mm applied with a stationary rain simulator, beyond a treatment without rain. Visual evaluations of control at 7 and 14 days had been carried through after application of the herbicides, counting of germinated plants and dry biomass of plants without application. The development of both weeds was inhibited by herbicides, reaching 100% of control, in all depth levels. The different rain blades had not influenced the control of the weeds. In the biggest depth of sowing (9,0 cm), the emergence was above 45% to B. decumbens and 36% to E. indica in treatments without herbicides application.

O objetivo deste trabalho foi o de avaliar o controle em pré-emergência das plantas daninhas capim-braquiária (Brachiaria decumbens) e capim-pé-de-galinha (Eleusine indica) em distintas profundidades no solo, pelos herbicidas oxyfluorfen e isoxaflutole, aplicados em condição de pré-emergência e submetidas a diferentes lâminas de chuvas. O delineamento experimental foi inteiramente casualisado, com quatro repetições. Cada parcela constou de um vaso de 4 L de capacidade, preenchido com solo arenoso, acrescido de sementes de capim-braquiária e capim-pé- galinha nas profundidades: 0,5, 1,0, 3,0, 6,0 e 9,0 cm. Utilizou-se a dose de 37,5 g i.a. ha-1 de isoxaflutole e 720 g i.a. ha-1 de oxyfluorfen. As lâminas de chuva foram 5, 10 e 20 mm aplicadas com um simulador de chuva estacionário, além de um tratamento sem chuva. Foram realizadas avaliações visuais de controle aos 7 e 14 dias após aplicação dos herbicidas, contagem de plantas germinadas e a biomassa seca das plantas sem aplicação de herbicidas. Os herbicidas inibiram o desenvolvimento de ambas as plantas daninhas, alcançando 100% de controle, em todos os níveis de profundidade. As diferentes lâminas de chuva não influenciaram o controledas plantas daninhas. Houve emergência acima de 45% para B. decumbens e de 36% para E. indica na maior profundidade de semeadura (9,0 cm) nos tratamentos sem aplicação de herbicidas.
Influence of rainfall depths on weed control, souned in different soil layers applying oxyfluorfen and isoxaflutole herbicides
Keywords: Brachiaria decumbens; Eleusine indica; Isoxaflutole; Stationary rain simulator; Oxyfluorfen; Brachiaria decumbens; Eleusine indica; Isoxaflutole; Simulador de chuva estacionário; Oxyfluorfen